Word mysteries & histories from quiche to humble pie - Moser, Barry; Claiborne, Robert; The American Heritage Dictionaries editor (Boston Houghton Mifflin, 1986)
Presents the etymology of over 500 words in the English language.
Illustrations and select commentary -- Editorial staff -- Foreword / by Robert Clairborne -- Preface -- The word mysteries and histories -- The last word -- Index.
Includes index.
Keywords: English language -- Etymology -- Dictionaries